Estimating allowable take for an increasing bald eagle population in the United States. Issue 2 (17th January 2022) - Zimmerman, Guthrie S.; Millsap, Brian A.; Abadi, Fitsum; Gedir, Jay V.; Kendall, William L.; Sauer, John R.
Abstract: Effectively managing take of wildlife resulting from human activities poses a major challenge for applied conservation. Demographic data essential to decisions regarding take are often expensive to collect and are either not available or based on limited studies for many species. Therefore, modeling approaches that efficiently integrate available information are important to improving the scientific basis for sustainable take thresholds. We used the prescribed take level (PTL) framework to estimate allowable take for bald eagles ( Haliaeetus leucocephalus ) in the conterminous United States. We developed an integrated population model (IPM) that incorporates multiple sources of information and then use the model output as the scientific basis for components of the PTL framework. Our IPM is structured to identify key parameters needed for the PTL and to quantify uncertainties in those parameters at the scale at which the United States Fish and Wildlife Service manages take. Our IPM indicated that mean survival of birds >1 year old was high and precise (0.91, 95% CI = 0.90–0.92), whereas mean survival of first‐year eagles was lower and more variable (0.69, 95% CI = 0.62–0.78). We assumed that density dependence influenced recruitment by affecting the probability of breeding, which was highly imprecise and estimated to have declined from approximately 0.988 (95% CI = 0.985–0.993) to 0.66 (95% CI = 0.34–0.99) between 1994 and 2018. We sampled values from the posterior distributions of the IPM for use in the PTL and estimated that allowable take (e.g., permitted take for energy development, incidental collisions with human made structures, or removal of nests for development) ranged from approximately 12, 000 to 20, 000 individual eagles depending on risk tolerance and form of density dependence at the scale of the conterminous United States excluding the Southwest. Model‐based thresholds for allowable take can be inaccurate if the assumptions of the underlying framework are not met, if the influence of permitted take is under‐estimated, or if undetected population declines occur from other sources. Continued monitoring and use of the IPM and PTL frameworks to identify key uncertainties in bald eagle population dynamics and management of allowable take can mitigate this potential bias, especially where improved information could reduce the risk of permitting non‐sustainable take. Abstract : We used the Prescribed Take Level framework to incorporate management objectives, risk tolerance, population size, and demographic rates to revise previous estimates of allowable take for bald eagles in the conterminous United States. We developed an integrated population model to provide stronger inferences from contemporary demographic data to inform the estimates of allowable take. The United States Fish and Wildlife Service can use the allowable take thresholds we provide for permitting take as specified in the Bald and Golden Eagle Protection Act.